MODEL PENGEMBANGAN SIKAP BERWIRAUSAHA DALAM UPAYA INOVASI PENGEMBANGAN USAHA MIKRO DI DESA - Pairan, Pairan; Samai, Samai; Gianawati, Nur Dyah; Partono, Partono (Journal of Social and Political Science, 2019)
The purpose of this study is to analyze the effort of innovational entrepreneurial attitudes in developing the ?Purnama? village microbusinesse. This descriptive qualitative research used the snowball techniques for determining informants. The data analysis technique applied the flow model that is data collection, data reduction, data presentation and drawing conclusions. The results of this study indicate that most families in the village are the bamboo craftswomen because the raw materials are easy to find as the most natural plantation resourse. The main product is ?besek? that is the box or bowl for fish container. The craftswomen sell the ?besek? to the collectors. Recently, the number of craftswomen is 350 which increased fastly from 50 persons relating to the market demand of ?besek?. This situation results the micro entrepreneurial attitudes which based on the process of making ?besek? for own need to crafts business. This family micro business innovate throught three (3) business constructions, they are input, envirounment, and output. Input is gained by increasing market demmand of ?besek? from another businessman who need ?besek?. Second is an environment which provides the raw materials and the craftswomen is the housewife who have craft skills. Last is outcome in the form of knowledge, attitudes, beliefs, values that grow after crafting entrepreneurship.Keywords: Development, Entrepreneurial Attitude, Micro Business, Village